A review of Erebomyia (Diptera: Dolichopodidae), with descriptions of three new species - Hurley, Richard L.; Runyon, Justin B. (Zootaxa, 2009)
The genus Erebomyia is reviewed and a key is provided for the four known species, three of which are described here: Erebomyia aetheoptera n. sp., E. akidoptera n. sp., and E. ramseyensis n. sp. The type species, E. exalloptera Runyon & Hurley, is redescribed and the male genitalia illustrated. Erebomyia is known from Arizona (3 spp.) and California (1 sp.), and males are notable for their modified wings, most exceptionally those of E. exalloptera whose left wing is of a different shape and size than the right wing. The occurrence of directional wing asymmetry in insects is reviewed to place the unique wings of E. exalloptera in context. Observations of Erebomyia courtship behavior are provided, and the potential adaptive significance of asymmetrical and modified wings of Erebomyia is discussed.